2016
DOI: 10.1007/s10886-016-0764-1
|View full text |Cite
|
Sign up to set email alerts
|

Adult Parasitoids of Honeydew-Producing Insects Prefer Honeydew Sugars to Cover their Energetic Needs

Abstract: To meet their carbohydrate requirements, adult parasitoids exploit a broad range of sugar resources, including floral and extrafloral nectar and honeydew. Although honeydew might be the predominant sugar source, especially in agricultural systems, it often is nutritionally inferior to sugar sources like nectar. Given its broad availability, it may be expected that sugar-feeding insects have evolved specialized adaptations to deal with this typically inferior sugar source. This would apply especially to organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…On the other hand, when aphids were present, the provision of additional resources did not increase A. ervi longevity, suggesting that the combination of honeydew and hosts is adequate to keep females alive. In fact, several studies have shown that parasitoids, including A. ervi, are well adapted to the use of insect-produced honeydew which is the predominant sugar source in many agricultural systems (Burger et al 2004, Lenaerts et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when aphids were present, the provision of additional resources did not increase A. ervi longevity, suggesting that the combination of honeydew and hosts is adequate to keep females alive. In fact, several studies have shown that parasitoids, including A. ervi, are well adapted to the use of insect-produced honeydew which is the predominant sugar source in many agricultural systems (Burger et al 2004, Lenaerts et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether the changes in nectar chemistry induced by the tested bacteria affected nectar consumption by the insects, a previously developed assay, using a capillary feeder (CAFE) system was used (Lenaerts, Abid, et al., ). Briefly, a plastic insect cage (height: 12.5 cm; diameter: 10.0 cm) was provided with four calibrated glass micropipettes (5.0 μl, Blaubrand Intramark, Wertheim, Germany) filled with 4.0 μl of the synthetic nectar solution and an overlay of inert mineral oil (1.0 μl) to minimize evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…In a third experiment, we assessed the effects of bacterial inoculation on insect longevity. The experiment was performed using the no‐choice CAFE assay outlined above (Lenaerts, Abid, et al., ), and was performed for a total of 225 parasitoid individuals divided over 15 cages, each with 15 individuals. Experiments were conducted under controlled conditions of 22°C, 70% relative humidity and with a 16:8 hr light:dark cycle, starting with the light period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When honeydew is present near their hosts, parasitoids have to invest less time in searching for sugar sources, and they can minimise energy and risks associated with searching for nectar, which may be located further away . Indeed, longevity of aphid parasitoids is generally supported by honeydew, but not all honeydew types are equal in this respect (Hogervorst et al, 2007;Tena et al, 2018), probably because some honeydew carbohydrates have a larger impact on longevity than do others (Lenaerts et al, 2016). Indeed, many factors contribute to variation in the composition of dietary sugars in honeydew, including host plant species (e.g.…”
Section: Introductionmentioning
confidence: 99%